Characteristics of Groundwater Level in the Szarvas-Békésszentandrás Oxbow Subbasin - Gombos, Béla; Szalókiné Zima, Ildikó; Csengeri, Erzsébet (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2022)
The shallow groundwater has a direct and indirect effect on natural vegetation and agricultural production. The decline in groundwater level (GWL) can have negative impacts. In many areas in Hungary decreasing GWL trends in the last decades were found by earlier studies. In our research we studied the characteristics of groundwater level focusing on our study area, the subbasin of Szarvas-Békésszentandrás Oxbow. We analysed 20 years daily data of groundwater level of eight monitoring wells. Annual course and long term tendencies of groundwater level were examined. In average of 16 years the GWL reaches its maximum in April and its deepest level in autumn (September, October and November depending on the station). Four typical groups of groundwater level courses could be distinguished based on the average depth and seasonal variations of GWL. The year to year GWL variability is larger in January and April compared to July and especially to October. The trends of the middle months of the seasons are almost the same in significance and slope compared to the trends based on yearly mean time series. The differences in trends can be found between stations rather than between the months used for calculations. The larger part of the subbasin can be characterised by decreasing trend in groundwater levels (2002-2020). The change exceeds 1 m at station Szarvas 2832 (144 cm) and Szarvas 2778 (122 cm). However, there is a station with no significant trend, GWL at Csabacsűd 2779 station shows relative stability in yearly average, which is valid for some areas in the eastern part of the subbasin.